2021
DOI: 10.1002/mds.28551
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes as a Determinant of Parkinson's Disease Risk and Progression

Abstract: A BS TRACT: Background: Type 2 diabetes (T2DM) and Parkinson's disease (PD) are prevalent diseases that affect an aging population. Previous systematic reviews and meta-analyses have explored the relationship between diabetes and the risk of PD, but the results have been conflicting. Objective: The objective was to investigate T2DM as a determinant of PD through a meta-analysis of observational and genetic summary data. Methods: A systematic review and meta-analysis of observational studies was undertaken by s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(94 citation statements)
references
References 72 publications
6
70
2
Order By: Relevance
“…The relatively low rate in PRISM might have been due to under-reporting among participants with well-controlled blood pressure. Previous evidence of a potential association between Type 2 diabetes and PD [24] was not supported by the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…The relatively low rate in PRISM might have been due to under-reporting among participants with well-controlled blood pressure. Previous evidence of a potential association between Type 2 diabetes and PD [24] was not supported by the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicates that insulin resistance causes changes in the micro-environment of the host striatum that could lead to effects on graft survival. Another study showed that the nigral dopaminergic neurons are more vulnerable to degeneration when exposed to the toxin MPTP in a mouse model of type 2 diabetes mellitus [53,54] consistent with many clinical studies suggesting aggravation of PD with existing comorbidity of diabetes [55][56][57]. The elevation of microglial density around the graft of the exendin-4 group/ + LD compared to exendin-4/-LD lends credence to this hypothesis, and accumulation of activated microglia around the graft has been shown to limit graft survival and function [7,58,59].…”
Section: Discussionsupporting
confidence: 68%
“… 13 , 33 Some studies agree that diabetes is a risk factor for Parkinson’s disease while other studies find no evidence of this association. 34–38 A meta-analysis from 2021 by Chohan et al 38 observed evidence for type 2 diabetes being positively associated with an increased risk of Parkinson’s disease. Nevertheless, we did not find this association in our analysis when investigating the effect of diabetes of all kinds or type 2 diabetes specifically.…”
Section: Discussionmentioning
confidence: 99%